Synchronization through frequency shuffling - Aravind, Manaoj; Pachaulee, Vaibhav; Sarkar, Mrinal; Tiwari, Ishant; Gupta, Shamik; Parmananda, P. (Physical review, 2024)
A wide variety of engineered and natural systems are modeled as networks of coupled nonlinear oscillators. In nature, the intrinsic frequencies of these oscillators are not constant in time. Here, we probe the effect of such a temporal heterogeneity on coupled oscillator networks through the lens of the Kuramoto model. To do this, we shuffle repeatedly the intrinsic frequencies among the oscillators at either random or regular time intervals. What emerges is the remarkable effect that frequent shuffling induces earlier onset (i.e., at a lower coupling) of synchrony among the oscillator phases. Our study provides a novel strategy to induce and control synchrony under resource constraints. We demonstrate our results analytically and in experiments with a network of Wien Bridge oscillators with internal frequencies being shuffled in time.
Online veröffentlicht: 21. Mai 2024
Gesehen am 15.01.2025